Variable stressor exposure shapes fitness within and across generations - Marcus Lee (Scientific Reports)
Abstract Environmental variation has long been considered a key driver of evolutionary change, predicted to shape different strategies, such as genetic specialization, plasticity, or bet-hedging to maintain fitness. However, little evidence is available with regards to how the periodicity of stressors may impact fitness across generations. To address this gap, I conducted a reciprocal split-brood experiment using the freshwater crustacean, Daphnia magna, and an ecologically relevant environmental stressor, ultraviolet radiation (UVR). I exposed one group to constant and another group to fluctuating UVR conditions. Despite receiving the same dose of UVR, the first experimental generation displayed significant treatment-by-genotype interactions with respect to survival and reproductive output, as well as a delayed reproductive maturity under fluctuating UVR conditions. In the following experimental generation individuals exposed to fluctuating UVR exhibited higher fitness than those in a constant UVR regime. The ancestral conditions, i.e., maternal environment, however affected the survival probability and reproductive output, but did not significantly influence the maturation date. Overall, I demonstrate that the delivery of a stressor, not just its intensity, can have profound fitness consequences across generations, with important implications for seasonal succession of genotype–phenotype patterns in natural environments.